INFLUENCE OF OVERBURDEN ON ECONOMICAL EXPLOITATION OF OPEN PITS - Kiril Grabowsky; Vladimir Rendulić (Rudarsko-geološko-naftni Zbornik, 1992)
From experience we have learnt that all efforts made in seeking thorough economical solutions in planning open pits are rewarding in the course of exploitation of the so planned open pits. From numerous issues to be solved in the course of planning the three are the most important, i.e. ultimate slope angle, waste transportation routes, and selection of equipment (the paper is published in Croatian).